Role of job Performance on the Job Satisfaction: A Study on the Elementary School Teachers - Pramanik, Dr. Bhabesh (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
This study examines the relationship between job performance and job satisfaction among elementary school teachers. Job satisfaction is crucial for employee well-being and organizational effectiveness, particularly in educational settings where teacher retention and performance directly impact student outcomes. Descriptive Survey research design has been applied in the current study. Population for the current study comprised of the Elementary school teachers working the district of Paschim Medinipur, West Bengal. Out of the existing population the researcher has selected a sample of 150 elementary school teachers by following the purposive sampling method for collecting the primary data. A teacher made job performance scale was developed to measure the performance level of the respondents on their respective jobs. Another structured questionnaire consisting of 20 statements was used for measuring the job satisfaction level of the Elementary school teachers. Collected data were tabulated and analyzed in the SPSS version 20 by applying the descriptive statistics and ANNOVA and Pearson Correlation Coefficient. The findings reveal that there is a weak positive relationship between job satisfaction and job performance and the job satisfaction has significant impact on the job performance.